SHAMANISM IS ONE OF THE FORMS OF HUMAN SELF-AWARENESS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article considers shamanism as one of the sources of philosophical thought of the Kyrgyz people. It is noted that shamanism is a special worldview system that includes elements of rational, irrational, and artistic-imaginative cognition of the world. Shamanism elevated an individual to the heights of the cosmos. Accordingly, he had a positive influence on the philosophical thoughts of the Kyrgyz.
Keywords: philosophy, society, nature, thought, man, shamanism, religion, knowledge, faith, people, consciousness.